2022
DOI: 10.3389/fcvm.2021.795750
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Associated Death of Ventricular Arrhythmia and Sudden Cardiac Death in Hospitalized Patients With COVID-19: A Systematic Review and Meta-Analysis

Abstract: BackgroundArrhythmia is a very common complication of coronavirus disease 2019 (COVID-19); however, the prevalence of ventricular arrhythmia and associated outcomes are not well-explored. Here, we conducted a systematic review and meta-analysis to determine the prevalence and associated death of ventricular arrhythmia and sudden cardiac death (SCD) in patients with COVID-19.MethodsDatabases of PubMed, Cochrane Library, Embase, and MdeRxiv were searched. Studies that could calculate the prevalence of ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…Several studies illustrated that the cardiac dysfunction parameter is significantly associated with all‐cause mortality in hospitalized patients with COVID‐19 66 and survivors of COVID‐19 67 . In a systematic review and meta‐analysis, Diaz‐Arocutipa et al 68 showed that among cardiac parameters, TAPSE was independently associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies illustrated that the cardiac dysfunction parameter is significantly associated with all‐cause mortality in hospitalized patients with COVID‐19 66 and survivors of COVID‐19 67 . In a systematic review and meta‐analysis, Diaz‐Arocutipa et al 68 showed that among cardiac parameters, TAPSE was independently associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In the present systematic review and meta-analysis, we performed a pooled analysis to evaluate the effect of SARS-CoV- indeed, reduced right ventricular function was reported as a risk factor for adverse events in community-acquired pneumonia, 64 as well as in patients with ventricular dysfunction. 65 Several studies illustrated that the cardiac dysfunction parameter is significantly associated with all-cause mortality in hospitalized patients with COVID-19 66 and survivors of COVID-19. 67 In a systematic review and meta-analysis, Diaz-Arocutipa et al 68 showed that among cardiac parameters, TAPSE was independently associated with higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…This is suggestive of severe hypoxia and critical illness being the main drivers of cardiac arrest. A multinational analysis of hospitalized COVID patients showed a pooled prevalence of ventricular arrhythmia to be 5% in the perimortem time 30 . Although less frequent when present, ventricular arrhythmias significantly contributed to an increased risk of death in those patients 31 , 32 .…”
Section: Cardiac Manifestations Of Covid-19mentioning
confidence: 99%
“…Thus, electrophysiology testing must be considered, especially in the pediatric population ( 68 ). There is evidence of an increased incidence of ventricular arrhythmias and SCD in COVID-19 patients ( 69 ), while a recent meta-analysis found a higher prevalence of SCD during the COVID-19 pandemic compared to the pre-pandemic period ( 70 ). Several mechanisms have been proposed to explain the possible association of SARS-CoV-2 infection with increased SCD risk and arrhythmogenesis, including direct myocardial injury, oxygen demand-supply mismatch due to hypoxia, hypercoagulability, and adverse effects of medications for COVID-19 ( 71 ).…”
Section: Discussionmentioning
confidence: 99%